Pharmacokinetics of pazufloxacin mesilate in patients with community-acquired pneumonia - Taguchi, Yoshio; Maniw, Ko; Abe, Noriyuki; Komatsu, Masaru (Japanese Journal of Chemotherapy, 2008)
We analyzed the concentration of pazufloxacin mesilate (PZFX) in the blood and evaluated its clinical effects. In seven patients (mean age: 71 years) with community-acquired pneumonia admitted and treated with PZFX. They experienced a total of eight episodes and their mean creatinine clearance was estimated at 64.7±35.4 mL/min. An intravenous drip-infusion of 500 mg of PZFX alone during a period of 30 minutes was administered every 12 hours. Blood sampling for therapeutic drug monitoring were conducted on treatment day 3. On day 3 of PZFX administration, data on fever, symptoms, and white blood cell count were obtained to evaluate clinical effects. Assessment of the eight episodes showed T1/2β to be 2.87±1.02 hr, Cmax 30.39±12.18μg/mL, and AUC 67.89±27.87 hr·μg/mL. PZFX treatment was clinically effective in seven episodes (87.5%). Fever disappeared in less than three days in four cases and less than five days in three cases. Cmax and AUC in this study were 1.7 to 3.1 times greater than reported in the phase I clinical study and studies conducted on the elderly. Statistical data is thus required reflecting individual disposition to appropriately use an antimicrobial with due consideration for its pharmacokinetics/pharmacodynamics because the disposition of an antimicrobial containing PZFX differs with the patient.